PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN PERUNDUNGAN - Rivki Andian; Mia Amalia; Aji Mulyana (Law Department Jenderal Achmad Yani University, 2024)
Bullying is an action carried out intentionally to cause harm physical, verbal, psychological by someone towards someone or a group of people against a person or group of people who feel helpless. Children victims of bullying must receive legal protection. Protection children as all activities to guarantee and protect children and their rights in order to live, grow, develop and participate optimally accordinglyper with human dignity, and receive protection from violence and discrimination. Government, parents, guardians, society and parties Schools have an obligation to provide character education and instilling good manners in children to prevent bullying.